THE ISSUE OF SCHEDULED TRIBE (ST) STATUS OF THE MATAKS OF ASSAM: AN ANALYSIS - Senapoti, Ishani (The journal of contemporary issues in business and government, 2021)
The Matak tribal people who has inhabited in a region known as Saumar prior to the invasion of Sukapha in 1228 AD has been neglected and disregarded in every spheres of life even today. Even after independence the Mataks were deprived of their due share in the society. In the post-independence period they had to struggle and fight for their due rights and opportunities. Under the banner of their voluntary, non-political organization they carried out their demands, memorandums and discussions with both the Central and State government and one of their significant demand is the Demand for Scheduled Tribe (ST) Plains status.